Measuring Resilience in Women with Endometriosis - Lubián-López, Daniel María; Moya-Bejarano, Davinia; Butrón-Hinojo, Carmen Aisha; Marín-Sánchez, Pilar; Blasco-Alonso, Marta; Jiménez-López, Jesús Salvador; Villegas-Muñoz, Emilia; González-Mesa, Ernesto Santiago (MDPI, 2021)
Endometriosis is a multifactorial disease with pathophysiological factors not yet well known; it also presents a wide symptomatic range that makes us think about the need for multidisciplinary management. It is a chronic disease in which there is no definitive treatment, and is associated in a large majority of cases with psychological pathology. Connecting comorbidities and multimorbidities on a neurobiological, neuropsychological, and pathophysiological level could significantly contribute to their more successful prevention and treatment. In our study, resilience is analyzed as an adjunctive measure in the management of endometriosis. Methods: A multi-centre, cross-sectional study was performed to analyse resilience levels in a sample of Spanish women suffering from endometriosis. CDRIS-25, CDRIS-10, BDI, the STAI, and the SF-36 Health Questionnaire were used for assessments. A representative group of 202 women with endometriosis was recruited by consecutive sampling. Exploratory and confirmatory factor analyses were performed for both resilience scales. Results: Mean CDRIS-25 and CDRIS-10 scores were 69.58 (SD 15.1) and 29.37 (SD 7.2), respectively. Women with adenomyosis and without signs of deep endometriosis showed the lowest scores. The best predictive model included women’s age, years of endometriosis evolution, number of pregnancies, and history of fertility problems as the best predictive factors. Conclusions: Women build resilience as the number of years of evolution of the disease increases. Symptoms such as dyspareunia and continued abdominal pain were more prevalent among less resilient women.
Keywords: Endometriosis; Resilience; Psychological disease